2019
DOI: 10.1002/cld.847
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation Using Steatotic Grafts

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/14-5-reading-jackson a video presentation of this article http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/14-5-interview-jackson the interview with the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Decisively, the outcome is better once a proper selection of patients is performed [10]. However, many surgeons have shown an augmented risk for inferior post-transplant outcomes in case of donor livers with moderate or severe large droplet macrosteatosis (ld-MaS), although donor livers with small droplet macrosteatosis (sd-MaS) or mild (<30%) ld-MaS are safe for transplantation [41,42]. The combined analysis confirmed that the degree of steatosis in donors' livers was below 3.5% avoiding the possibility of having a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Decisively, the outcome is better once a proper selection of patients is performed [10]. However, many surgeons have shown an augmented risk for inferior post-transplant outcomes in case of donor livers with moderate or severe large droplet macrosteatosis (ld-MaS), although donor livers with small droplet macrosteatosis (sd-MaS) or mild (<30%) ld-MaS are safe for transplantation [41,42]. The combined analysis confirmed that the degree of steatosis in donors' livers was below 3.5% avoiding the possibility of having a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…While declining the offer of a steatotic liver has been shown to increase an individual’s waiting list mortality [41], the unpredictable response of steatotic livers to reperfusion, with an increased severity of ischaemia‐reperfusion injury (IRI) and subsequently increased rates of PNF, EAD and post‐liver transplant acute kidney injury mean that there is an understandable reluctance to routinely transplant such livers [21,42]. As the demand for organ transplantation continues to remain high and the epidemic of obesity in the west is resulting in higher rates of steatosis in donor organs [43,44], we will inevitably need to implant more steatotic livers in the future. Others have shown that one possible solution to overcoming the excess risk of a steatotic organ is to allocate steatotic organs to ‘preferred recipients’ (defined as first‐time recipients with a MELD 15‐34, without primary biliary cirrhosis and not on life support prior to transplantation), as these recipients have no significant increase in mortality or graft loss when receiving steatotic compared to nonsteatotic livers [45].…”
Section: Discussionmentioning
confidence: 99%
“…United Network for Organ Sharing region of transplant and year of transplant were included in all regression modeling, both of which have previously been shown to influence organ utilization and outcomes among highly steatotic organs. 9 , 14 All statistical analyses were performed using JMP Pro 14.1 software (SAS Institute Inc., Cary, NC). P values <0.05 were considered significant.…”
Section: Methodsmentioning
confidence: 99%